2013 IEEE 63rd Electronic Components and Technology Conference 2013
DOI: 10.1109/ectc.2013.6575549
|View full text |Cite
|
Sign up to set email alerts
|

Generic rules to achieve bump electromigration immortality for 3D IC integration

Abstract: An immortal solder micro-bump (bump) electromigration (EM) lifetime has been demonstrated for 3D IC integration. This ultimate goal was achieved under strictly controlled conditions, including the optimal design of bump metallurgy, geometry, optimized processes, along with welldefined stressing conditions and manufacturing window. The current carrying capability and EM lifetime of bump have been investigated as functions of stressing conditions which are correlated with the degradation mechanisms. When stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…27 Lin et al stressed microbumps at 1.23 Â 10 5 A/cm 2 at an ambient temperature of 130 C and they detected concave-down resistance curves. 28 Similar results were also found in 5 lm-thick-solder microbumps with 30 lm pitch stressed at 10 4 -10 5 A/cm 2 at 150 C. 29 Chen et al also reported a fast initial rise in resistance, then gradually taper-off and reaches a steady state after prolonged stressing in microbumps stressed under 1.0 Â 10 5 A/cm 2 at 140 C. 30 However, there have been no studies addressing this interesting phenomenon and the discrepancy in results.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…27 Lin et al stressed microbumps at 1.23 Â 10 5 A/cm 2 at an ambient temperature of 130 C and they detected concave-down resistance curves. 28 Similar results were also found in 5 lm-thick-solder microbumps with 30 lm pitch stressed at 10 4 -10 5 A/cm 2 at 150 C. 29 Chen et al also reported a fast initial rise in resistance, then gradually taper-off and reaches a steady state after prolonged stressing in microbumps stressed under 1.0 Â 10 5 A/cm 2 at 140 C. 30 However, there have been no studies addressing this interesting phenomenon and the discrepancy in results.…”
Section: Introductionsupporting
confidence: 57%
“…This behavior was also reported in several previous studies. [27][28][29][30] To investigate the reason behind the different behaviors of the resistance curve, FEA modeling was carried out. The structure of the solder joint was almost identical to the one in Fig.…”
Section: -2mentioning
confidence: 99%
See 2 more Smart Citations
“…And several studies have reported that the bump geometry of fine pitch micro joining using Sn-Ag solder after electromigration test [6,7]. But fine pitch micro bump using a SnBi solder has been little investigated [8].…”
Section: Introductionmentioning
confidence: 99%